Multiple quantum structures as an active region for GaAs-based p-i-n photodetector - Presto, Jorge Michael Macabinquil (National Institute of Physics, College of Science, University of the Philippines Diliman, 2010)
Room temperature (300K) responsivity and dark current measurements of MBE grown p- n(AlGaAs), p-i-n(InGaAs MQW) and p-i-n(InAsQDs, InGaAs QW, GaAs QW) photodetectors prepared on n+-GaAs substrate are investigated. Maximum responsivity of 1.0 A/W at 880 nm wavelength and detection range extending to 1,170nm are observed for p-i-n- sample with multiple quantum structures as the active region. Quantum-Confined Stark Effect is demonstrated by the observed shifting and broadening of the GaAs quantum well excitonic peaks. Significant reduction on the dark current is also observed by inserting an AlGaAs blocking layer within the active region of the p-i-n photodetector with multiple quantum structures. The results showed the effectiveness of the methodology introduced to widen the detection range and at the same time lower the dark current of photodetectors at room temperature.